The genus Ctenorillo Verhoeff, 1942 (Oniscidea, Armadillidae) from Colombia: new records, new species, and conservation comments - Carpio-Díaz, Yesenia M.; López-Orozco, Carlos Mario; Borja-Arrieta, Ricardo; Gutierrez-Estrada, Miguel; Campos-Filho, Ivanklin Soares; Sfenthourakis, Spyros; Taiti, Stefano; Neita Moreno, Jhon Cesar; Bermúdez, Adriana; Navas S., Gabriel R.; Bichuette, Maria Elina (Tropical zoology, 2023)
The Armadillidae are the most diverse family within the Oniscidea, widely distributed around the world. To date, only seven species of the family are known from Colombia. After the examination of a collection from the Colombian departments of Atlántico, Bolívar, Cesar, Magdalena, Risaralda, Santander, and Sucre, eight species were recognized as belonging to the genus Ctenorillo, of which six are considered to be new to Science: C. binomio n. sp., C. humboldti n. sp., C. mincaensis n. sp., C. orientalis n. sp., C. papagayoensis n. sp., and C. tayrona n. sp. Moreover, the distribution knowledge of C. dazai and C. tuberosus has expanded. Ctenorillo species in Colombia are predominantly distributed in Tropical Dry Forest areas, which is one of the most endangered ecosystems in the world. Considering the new taxa presented here, allied with other Oniscidea groups, there is an urgent need to raise the awareness level regarding the conservation status of this ecosystem in the country.